Occurrence and Genesis of Palygorskite and Associated Clay Minerals in a Pleistocene Calcrete Complex, Sde Boqer, Negev Desert, Israel - Verrecchia, Eric; Le Coustumer, M.-N. (My University, 1996)
Palygorskite and associated clay minerals have been studied in a Pleistocene calcrete complex from the Negev desert (Sde Boqer, Israel). This complex is divided into five main parts: the chalky and marly bedrock overlain by its weathered product, a brecciated calcrete hardpan; the laminar crust; loess pockets trapped in the calcrete; and the overlying soft surficial soil. The distribution of clay minerals is directly dependent on the position of the sample in the calcrete complex. Smectite is inherited from the bedrock in the calcrete with an aeolian enrichment in loess pockets and upper soft soil. The source of kaolinite is mainly detrital, related to desert dust. Illite is partly inherited and partly neoformed in loess pockets and desert surficial soil. The origin of palygorskite is clearly related to precipitation processes from soil solutions, Si and Al ions being provided by the slope and detrital grains trapped in the calcrete, with Mg being provided by the parent rock, the slope and aeolian detrital dolomite. This neoformation occurs mainly around detrital grains such as quartz in the hardpan and along textural transitions in loess pockets and is associated with gypsum in the lower part of the toposequence where the evaporation fluxes are the most important. The existence as coatings around grains and the delicate structure of the fibres are incompatible with a detrital origin. Moreover, no evidence was found to support any transformation of smectite into palygorskite in the solid state. Palygorskite is the last step of the cycle of mobile silica and seems to be a product of late diagenesis in Sde Boqer calcrete.